2007
DOI: 10.1073/pnas.0700182104
|View full text |Cite
|
Sign up to set email alerts
|

Needle-free delivery of macromolecules across the skin by nanoliter-volume pulsed microjets

Abstract: Needle-free liquid jet injectors were invented >50 years ago for the delivery of proteins and vaccines. Despite their long history, needle-free liquid jet injectors are not commonly used as a result of frequent pain and bruising. We hypothesized that pain and bruising originate from the deep penetration of the jets and can potentially be addressed by minimizing the penetration depth of jets into the skin. However, current jet injectors are not designed to maintain shallow dermal penetration depths. Using a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 23 publications
1
89
0
1
Order By: Relevance
“…This recent methodology can be used to painlessly deliver a relatively small volume of drug (usually 0.2-1 ml) within a few hundredths of a second either subcutaneously, intramuscularly, or intradermally (Baxter and Mitragotri, 2006;Arora et al, 2007). More importantly, needle-free injection offers more reliable depth of penetration and more efficient use of the drug, thereby requiring the use of significantly less drug and lowering costs.…”
Section: F Current Status Of Adjudin Researchmentioning
confidence: 99%
“…This recent methodology can be used to painlessly deliver a relatively small volume of drug (usually 0.2-1 ml) within a few hundredths of a second either subcutaneously, intramuscularly, or intradermally (Baxter and Mitragotri, 2006;Arora et al, 2007). More importantly, needle-free injection offers more reliable depth of penetration and more efficient use of the drug, thereby requiring the use of significantly less drug and lowering costs.…”
Section: F Current Status Of Adjudin Researchmentioning
confidence: 99%
“…Similarly, the geometry of micro-injections shown in the imaging cross-sections of Fig. 3a, with a thin injected column of ink capped with a larger volume on the gelatin surface, differs from the usual puncture and dispersion profile of existing needle-free microjet injectors [9,10,13]. This difference might result from the stiffer injected materials used in these previous studies, whose stiffness tend to disperse sideways the injections.…”
Section: Depth-controlled Injection For Direct Three-dimensional Liqumentioning
confidence: 53%
“…Such microjet injectors were designed to run in a repetitive [9,10] way through piezo-actuation, and studies demonstrated that this approach allows volumes with a dose precision in the nanoliter range (2-30 nL) to be delivered. Doses could further be injected locally at a frequency larger than 1 Hz within an area > 100 μm in diameter, which we define as the lateral resolution of injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to springs and compressed air, alternative driving forces have been explored in order to transform the one-time jet injection into an intermittent micro-jet injection. The micro-jet injection system was first proposed by Arora, et al [2]. It applied a piezoelectric stack actuator as the driving power.…”
Section: Introductionmentioning
confidence: 99%